2020
DOI: 10.1038/s41419-020-2343-1
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow inhibits the Hippo/YAP pathway via autophagy and SIRT1-mediated deacetylation against atherosclerosis

Abstract: Atherosclerosis is a multifactorial disease of the vasculature, and shear stress is a crucial regulator of its process. Disturbed flow promotes atherosclerotic effects, while laminar flow has a protective action on the endothelium. Hippo/YAP is a major cascade that senses various mechanical cues and mediates the expression of pro-inflammatory genes. However, the mechanism modulating the transcription factor YAP in response to different patterns of blood flow remains unclear. In this study, we provide evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 26 publications
(37 reference statements)
1
67
0
Order By: Relevance
“… Shi et al 140 DCM Streptozotocin constructed diabetic model in endothelium-specific MST1 Tg mice CMEC/cardiomyocyte The MST1-enriched exosomes released from CMECs inhibit autophagy and glucose metabolism, thereby promote apoptosis in cardiomyocyte. Yuan et al 141 Atherosclerosis ApoE −/− mice HUVECs Laminar flow protects the endothelium, inhibits Hippo-YAP signaling by promoting endothelial autophagy and SIRT1 expression, and blocks the formation of atherosclerotic plaques. Wang et al 142 Atherosclerosis ApoE −/− : Mst1 −/− and ApoE −/− : Mst1 Tg mice Murine macrophage In ApoE ( −/− ) mice, MST1 may stabilize atherosclerotic plaques by inhibiting macrophage autophagy and promoting macrophage apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“… Shi et al 140 DCM Streptozotocin constructed diabetic model in endothelium-specific MST1 Tg mice CMEC/cardiomyocyte The MST1-enriched exosomes released from CMECs inhibit autophagy and glucose metabolism, thereby promote apoptosis in cardiomyocyte. Yuan et al 141 Atherosclerosis ApoE −/− mice HUVECs Laminar flow protects the endothelium, inhibits Hippo-YAP signaling by promoting endothelial autophagy and SIRT1 expression, and blocks the formation of atherosclerotic plaques. Wang et al 142 Atherosclerosis ApoE −/− : Mst1 −/− and ApoE −/− : Mst1 Tg mice Murine macrophage In ApoE ( −/− ) mice, MST1 may stabilize atherosclerotic plaques by inhibiting macrophage autophagy and promoting macrophage apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…For immunoprecipitation experiments, 2 mg of cell lysate was incubated with specific antibodies and immobilized on protein A/G PLUS-agarose beads (Santa Cruz Biotechnology). Proteins were separated by SDS-PAGE, transferred to a nitrocellulose membrane and blotted with specific antibodies, including those against RAS (1:300, Thermo Fisher Scientific, #16117) 25 , GEF H1 (1:500, Abcam, ab155785) 26 , RASA1 (1:500, Abcam, ab2922) 27 , Ac-lysine (1:500, Abcam, ab21623) 28,29 , phospho-AKT (Ser-473, 1:500, Cell Signaling, #4051) 30 , AKT (1:500, Cell Signaling, #2920) 31 and β-actin (1;1000, Thermo Fisher Scientific, #AM4302) 32 , for western blotting.…”
mentioning
confidence: 99%
“…Kheloufi et al further revealed that high shear force boosts autophagy in ECs, and endothelial autophagy inhibits EC apoptosis, aging, and inflammation, collectively suppressing the formation of atherosclerotic plaques (81). The latest study demonstrates that LF induces YAP nuclear export mediated by SIRT1-dependent deacetylation and degradation through autophagy, and subsequently inhibits atherogenesis (193).…”
Section: Shear Stress and Ec Autophagymentioning
confidence: 97%